Comparative evaluation of magnetic resonance arthrogram with arthroscopy in knee pathologies - Harish Deepak P; Prem Chand Paladugu; Boblee James (Asian Journal of Medical Sciences, 2023)
Background: Magnetic resonance arthrogram (MRA) has emerged as a supplement to non-contrast magnetic resonance imaging (MRI), especially in the identification of meniscal and chondral pathologies. It has increased the diagnostic efficacy of MRI in the evaluation of knee pathologies.